612 The effect of household size on injury risk factors in Southern Brazil. (1st September 2016) - Toomey, Nicole; El-Gabri, Deena; Vissoci, João Ricardo; Staton, Catherine
Abstract : Background: The neighbourhood an individual lives in affects their injury risk. In Brazil, males of minority races with low education have the highest risk for injury. Family is an important aspect of Brazilian culture; however there is little research on how family structure affects injury risk. This preliminary analysis investigates the association between household size and risk for types of injuries. Methods: Information on household demographics was collected in a survey on treatment-seeking behaviour following injury in Maringá, Brazil between May and September 2015. The prevalence of demographic factors, including insurance status, mode of transportation to health care, and education level, as well as reasons for not seeking care, were analysed by three categories of household size: 2 or fewer individuals, 3 to 5 individuals, and 6 or more individuals. Frequencies, range, and odds ratios were reported. Results: Of 2678 households, the mean household size was 3.39 (r 1–15). As household size increased, enrollment in private insurance decreased; 50.5% of households of 2 or fewer had private insurance compared to only 27.5% with 6 or more. Alcohol usage prior to injury increased with household size; 5.3% of individuals in households of 2 or fewer reporting use, compared and 9.8% in houses of 6 or more. Large households had higher odds of unspecified injuries (OR: 1.85), including acts of violence, compared to households with 5 or fewer members. Odds of burn decreased with household size increase (OR: 0.833). Conclusions: Household size is a component of socioeconomic status; our data shows it is associated with insurance and alcohol usage. Risk of certain injuries is associated with household size. Further research needs to assess where these injuries are occurring, such as work or home. More in-depth research is also needed on how household size affects the family member occupations, as this places them at higher risks for different forms of injuries.